Method of Binary Structures Compression on Basis of Cascade Encoding in Telecommunication Systems - Barannik, Vlad.; Hahanova, A. V. (ХНУРЭ, 2012)
Grounded, that due to presentation of binary array as integral structure as a cascade structural number, additional reduction of structural surplus is provided. A cascade structural number is the number which satisfies limits on the number of units carouses and on the dynamic range of one-dimensional floating structural numbers (OSN) codes. The theorem is proved about forming of cod-number for a cascade structural number. It is shown, that amount of digits on presentation of binary column, which is examined as an element of cascade structural number less than, amount of digits on presentation of that column, but examined as a onedimensional floating structural number.
Keywords: one-dimensional floating structural numbers; cascade structural number